2017
DOI: 10.18554/reas.v6i1.1503
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico De Pacientes Com Hiv/Aids Do Estado Do Paraná: Estudo Ecológico

Abstract: Objetivo: realizar o levantamento do perfil epidemiológico dos pacientes com HIV/AIDS do estado do Paraná. Método: trata-se de um estudo ecológico que utilizou como unidade de análise os 399 municípios do Estado do Paraná nos quais são operacionalizados pelas ações do Programa Estadual de Controle da DST/AIDS e Hepatites Virais, analisando o perfil epidemiológico do Sistema Nacional de Vigilância em Saúde 2011. Resultados: o primeiro caso de AIDS registrado no Paraná foi em 1984, até junho de 2010, foram regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
4
0
6
Order By: Relevance
“…This can cause emotional discomfort and guilt in these mothers, as they cannot breastfeed and then "fail" to contribute to the beneficial aspects of breastfeeding the baby. 3 These women suffer at first for not breastfeeding and then for condemning HIVpositive serology in the face of fear of stigma and social discrimination. Thus, it becomes possible to realize that social charging puts them in awkward situations.…”
Section: Know This Disease Is To Build the Name Of The Lord; I Knowmentioning
confidence: 99%
See 3 more Smart Citations
“…This can cause emotional discomfort and guilt in these mothers, as they cannot breastfeed and then "fail" to contribute to the beneficial aspects of breastfeeding the baby. 3 These women suffer at first for not breastfeeding and then for condemning HIVpositive serology in the face of fear of stigma and social discrimination. Thus, it becomes possible to realize that social charging puts them in awkward situations.…”
Section: Know This Disease Is To Build the Name Of The Lord; I Knowmentioning
confidence: 99%
“…It is reported that, at this time, there was no complete knowledge as to the cause of the disease, as it was supposed to be related to the compromise of cellular immunity related to risky sexual behaviou and homosexual relations. [2][3] It is noted that in that same decade, Brazil was also hit by an HIV epidemic that, at first, affected homo and bisexual men and hemophiliacs and, later, injecting drug users. Since then, there has been a change in the epidemiological profile of people with HIV, the feminization of this epidemic, that is, the rapid increase in cases among women, with high rates of seropositive pregnant women being cataloged, a factor considered to be a public health problem through the possible vertical transmission of HIV.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A epidemia de HIV/AIDS é um acontecimento global, enérgico e instável que passa por um acúmulo de sub epidemias regionais. É consequência das disparidades da sociedade brasileira em que o alastramento da contaminação pelo HIV e AIDS expõe as expressivas mudanças do seu perfil epidemiológico (Sales, et al, 2017).…”
Section: Introductionunclassified